2018
DOI: 10.1002/pchj.257
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the effect of implementation intention on prospective memory

Abstract: Prospective memory (PM) refers to the ability to remember to do something in the future. Implementation intention refers to a self‐regulatory strategy in the form of “If …, then …” planning that can improve PM performance. However, the neural basis of the effect of implementation intention on PM remains unclear, as do the phases of PM that are affected by implementation intention. This study aimed to address these issues. Healthy participants were randomly assigned to the implementation intention (n = 18) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…In addition, the performance of time-point and time-period prospective memory of school-age children continues to develop with age. This shows that clear external time cues are more helpful in improving the performance of the time-point prospective memory of school-age children, which verifies the previous research results [ 58 , 59 ]. At the same time, the two types of prospective memory abilities of school-age children do not develop in sync, and the time-period prospective memory ability mainly concentrates on the stage of 7- to 9-year-old children.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the performance of time-point and time-period prospective memory of school-age children continues to develop with age. This shows that clear external time cues are more helpful in improving the performance of the time-point prospective memory of school-age children, which verifies the previous research results [ 58 , 59 ]. At the same time, the two types of prospective memory abilities of school-age children do not develop in sync, and the time-period prospective memory ability mainly concentrates on the stage of 7- to 9-year-old children.…”
Section: Discussionsupporting
confidence: 90%
“…This indicates that the participants could selectively and dynamically invest the attention resources into different task stages based on the time information during the implementation of MPM. Chen et al (2014) further used the event-related potential technology to verify that the processing mechanism of MPM was different from EBPM, showing the characteristics of dynamic and flexible attention allocation. According to the above evidence, MPM has additional time cues compared with EBPM.…”
Section: Introductionmentioning
confidence: 99%
“…69 BA 8R could participate in memory retrieval and could respond to related stimuli. 70 Taken together, BA 7L-BA 19L…”
Section: Cortical Functional Connectivity In Each Microstate Of Doc P...mentioning
confidence: 86%
“… 69 BA 8R could participate in memory retrieval and could respond to related stimuli. 70 Taken together, BA 7L–BA 19L and BA 10R–BA 8R may have indicated that VS patients were not unconscious when faced with pain or stimuli, but could activate relevant brain regions and respond to stimuli.…”
Section: Discussionmentioning
confidence: 98%